Evaluating the association of free sugars intake and glycemic load on cardiometabolic outcomes: A prospective analysis throughout adolescence into early adulthood - Marinho, AR (2020)
Purpose: To prospectively evaluate the relation of free sugars intake and glycemic load with adiposity and insulin resistance, from adolescence into early adulthood. Methods: Data from the population-based cohort EPITeen (Porto, Portugal) at 13 and 21 years old was used (n = 1034). At both ages, dietary assessment was obtained by food frequency questionnaires (FFQ). Added sugar of each food item was estimated based on a systematic methodology described by Louie et al. Free sugars (FS) were defined according to World Health Organization. To each food item of the FFQ, a calculated mean value of FS and glycemic index was assigned. Dietary glycemic load (GL) was determined for each participant. Sex- and age-specific body mass index z-score (BMIz) and waist-to-weight ratio (WWr) were used as measures of adiposity, and the homeostasis model assessment (HOMA-IR) as a measure of insulin resistance. A cross-lagged path analysis was performed to examine causal relationships between FS intake or dietary GL with BMIz, WWr or HOMA-IR. Results: No significant association was found between intake of FS and dietary GL at 13 years with BMIz, WWr or HOMA-IR at 21. A significant inverse association was found between BMIz at 13 and FS (β = -0.595,95%CI -0.830, -0.359) and dietary GL (β = -0.687,95%CI -0.937,-0.437) at 21 years. Intake of FS, dietary GL, as well as BMIz, WWr and HOMA-IR tracked from 13 to 21 years. Conclusion: No significant association was found between consumption of FS and GL at 13 years with cardiometabolic features at 21 years. Dietary intake and cardiometabolic outcomes tracked from adolescence into early adulthood.